Penguatan Literasi Kesehatan Ibu Hamil Melalui Edukasi Gizi dan Pencegahan Anemia di Wilayah Kerja Puskesmas Kuta Baro Kabupaten Aceh Besar - Quranayati Quranayati; Srie Wahyuni; Meylissa Meylissa; Maini Maini (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
Anemia among pregnant women remains a major public health problem, increasing the risk of pregnancy and childbirth complications, low birth weight, preterm birth, and maternal and neonatal mortality. Low health literacy regarding adequate nutrition, iron and folic acid supplementation (IFAS), and anemia prevention contributes to its high prevalence. This community service program aimed to improve pregnant women's health literacy through nutrition education and anemia prevention. Activities included interactive health education, group discussions, demonstrations on selecting iron-rich foods, educational leaflet distribution, and pre-test and post-test evaluations. Conducted at a community health center (Puskesmas), the program involved 30 pregnant women. Participants' mean knowledge score increased from 64.2 to 88.6 after the intervention. They also demonstrated better understanding of regular IFAS consumption, iron-rich food selection, and anemia prevention during pregnancy. Active participation reflected the effectiveness of the educational approach. This program is expected to encourage healthier anemia prevention behaviors, support healthy pregnancies, and contribute to reducing stunting risk during the First 1,000 Days of Life